Help-seeking during 1-year follow-up in Chinese patients diagnosed with type 2 diabetes mellitus comorbid major depressive disorder - Geng, Wenqi; Jiang, Yinan; Hong, Xia; Zhao, Weigang; Ren, Jie; Lloyd, Cathy; Sartorius, Norman; Wei, Jing (Frontiers in Endocrinology, 2023)
Introduction: Previous research has revealed a bidirectional relationship between type 2 diabetes mellitus (T2DM) and major depressive disorder (MDD). A very limited proportion of patients with T2DM comorbid MDD received adequate psychiatric intervention. This study investigated the helpseeking behaviors of patients with T2DM comorbid with MDD during one-year follow-up.Methods: At a medical center in China, a cohort of outpatients with T2DM were assessed and diagnosed for comorbid depression at baseline and after one year. The Mini International Neuropsychiatric Interview was used to diagnose MDD, while The Patient Health Questionnaire-9 (PHQ-9) and The Hamilton Depression Scale 17-item (HAMD-17) were used for depression assessment. Mental health help-seeking behaviors of patients during follow-up period were also evaluated.Results: Out of the 203 patients with T2DM at baseline, 114 (56.2%) completed the follow-up. The prevalence of MDD in participants with T2DM was 12.8% at baseline and 22.8% at follow-up. Patients who completed the follow-up had a lower baseline PHQ-9 score (test statistic -2.068, p=0.039), HAMD-17 score (test statistic -2.285, p=0.022) than those who did not complete the follow-up. A total of 26 patients had comorbid MDD during the follow-up period, among which 8 patients (30.8%) voluntarily visited psychiatric clinics, while others did not seek assistance. The level of HbA1c at follow-up was higher in patients who sought help than in those who did not (8.1±1.8% vs 7.0±0.7%), although the difference was not statistically significant.Conclusions: Voluntary psychiatric help-seeking for Chinese patients with comorbid T2DM and MDD is uncommon. It is crucial to increase awareness of depression among patients and healthcare professionals alike.